Effects of pulmonary rehabilitation on quality of life and exercise tolerance - Betancourt-Peña, Jhonatan; Ávila-Valencia, Juan Carlos; Muñoz-Erazo, Beatriz Elena; Hurtado-Gutiérrez, Hugo; Benavides-Córdoba, Vicente (Universidad y Salud, 2020)
Introduction: Pulmonary rehabilitation is an intervention that decreases the symptoms of chronic obstructive pulmonary disease (COPD). PR also improves exercise tolerance, emotional state, and functionality. Pulmonary rehabilitation leads to participation and perception of control of the disease, which ultimately enhances the quality of life. Objective: To describe the effects of PR on quality of life and its influence on the functional aerobic capacity in patients with COPD. Materials and methods: A quasi-experimental study was conducted with patients who attended PR. Functional aerobic capacity was assessed by a 6-minute walking test. The St. George Respiratory (SGRQ) and the Chronic Respiratory Disease (CRQ-SAS) Questionnaires were used to assess health-related quality of life. Results: There was a significant improvement in the 6-minute walking test. Based on the SGRQ, the categories of activity, symptoms, impact, and the total score revealed significant improvements (p≤ 0,005). Finally, the CRQ-SAS registered a positive effect of PR on the domains dyspnea, emotional and total score (p<0,001). Conclusions: PR improves quality of life and functional aerobic capacity of COPD patients.